2018
DOI: 10.3758/s13420-018-0327-0
|View full text |Cite
|
Sign up to set email alerts
|

Incidental spatial memory in the domestic dog (Canis familiaris)

Abstract: We built upon previous work by Fujita et al. (2012, Animal Cognition, 15(6), 1055-1063) to create an experiment that investigated the presence of incidental memory for the spatial location of uneaten food in the domestic dog. Here, we dissociated potentially incidental spatial memory from the incidental memory for the characteristics of objects, in this case, food bowls. Eighteen household domestic dogs of various breeds and age were presented with four bowls. Each bowl contained either a novel object, treats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In these studies, the authors emphasized that recalling an event can only be considered an episodic memory if the event was encoded incidentally. That is, information from the event must have been encoded without knowing that it must be remembered later (Singer & Zentall, 2007; Sluka et al, 2018; Zentall, Singer, & Stagner, 2008; Zhou, Hohmann, & Crystal, 2012). Unexpected tests were used to encourage incidental encoding in Experiments 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the authors emphasized that recalling an event can only be considered an episodic memory if the event was encoded incidentally. That is, information from the event must have been encoded without knowing that it must be remembered later (Singer & Zentall, 2007; Sluka et al, 2018; Zentall, Singer, & Stagner, 2008; Zhou, Hohmann, & Crystal, 2012). Unexpected tests were used to encourage incidental encoding in Experiments 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…They can rear sheep, rescue victims, and provide safety to others. One limited study of 18 household dogs found that they lacked spatial memory and were more focused on the "what" of a task rather than the "where" [55]. Another study of canine cognitive abilities found that dogs' capabilities are no more exceptional than those of other animals, such as horses, chimpanzees, or cats [56].…”
Section: Human and Animal Continuum Of Knowledge And Awarenessmentioning
confidence: 99%
“…Take dogs as an example, we recognize their ability to rear sheep, rescue victims, providing safety and be helpers to humans or their owners. However, one limited study of 18 household dogs found that they lacked spatial memory and were more focused on the "what" of a task rather than the "where" [56]. Another study of canine cognitive abilities found that dogs' capabilities are no more exceptional than those of other animals, such as horses, chimpanzees, or cats [57].…”
Section: Human and Animal Continuum Of Knowledge And Awarenessmentioning
confidence: 99%